Pengaruh Tingkat Pendidikan dan Konsumsi terhadap Kuantitas Penduduk Miskin di Jawa Tengah - Umami, Nabila (Universitas Indraprasta PGRI, 2024)
The percentage of the quantity of the poor population in Central Java for the 2017-2021 period tends to still fluctuate even though there has been a low increase. Even though the quantity of the poor population in Central Java province decreased by 0.21 percent, Central Java is the region that experienced the smallest reduction in the quantity of the poor population when compared to West Java province, which decreased by 0.34 percent and East Java, which decreased by 1.02 percent. percent. This research explores the influence of education and consumption levels on the quantity of poor people in Central Java with the total population covering all data in Central Java from 2017 -2021. The saturated sampling technique was applied as a data collection process that investigated the entire population of 35 districts and cities in Central Java. The data taken is secondary data sourced from published data from the Central Java Central Statistics Agency by applying documentary methods and panel data regression as data analysis techniques. Proving the data test using the Fixed Effect Model (FEM) as a preference which is then followed by classical assumption testing as well as statistical criteria testing using the help of Eviews version 12 software. Based on the results of this study, the findings are that: 1) The level of education has an insignificant positive effect on quantity poor people in Central Java; 2) Consumption has a significant negative effect on the quantity of poor people in Central Java.